Caminho Sonoro: O corpo em escuta performativa - AMÉRICO, Waléria. (Universidade Federal do Pará, 2025)
The Sound Path deals with the relationship between body and landscape, using displacement as a space for artistic creation. The body in front of the river-forest horizon aimed to develop sonorities over the duration of the path. Procedures of listening to the soundscape, drawing scores and collaborating with people and natural beings make up the performances or sound transmissions. The reflection starts with the writing of experimental between places and the practice of listening to the soundscape in the north of Brazil, in the capital Belém, located in the state of Pará. The experience of the body in the Amazonian territory blossomed into art actions in resonance with the Samaúma tree species.